Devil’s in the Detail: How to assess transformation of ownership of the South African private sector - Joubert, Michelle (Southern Centre for Inequality Studies (SCIS), 2021)
This paper explores listed and unlisted equity ownership in the context of the distribution of South Africa’s national wealth. It is intended to contribute to a shared understanding of private sector ownership: how South Africans hold equity, how equity wealth is distributed among South African households, and transformation of ownership of equity ownership. This includes the listed segment, a crucial part of the bigger picture, as well as unlisted business. It also explores where ownership information is found and could be accessed in future. The hope is that this assessment will contribute to a broader discussion on accelerating transformation.
Keywords: Black Economic Empowerment; South African private sector; South Africa’s national wealth